Structural analysis of silk proteins using x–ray and neutron scattering - Greving, I (2012)
The silk fibres spun by insects and spiders have intrigued scientists for many years. Their mechanical performance is remarkable when one considers that the fibres are spun under ambient conditions from aqueous protein solutions without requiring many of the harsh processing conditions used in the production of man-made fibres. Yet, despite this interest, very little is known about the initial structure of the precursor proteins prior to spinning. One reason for this lies in the difficulty of handling the native proteins without accidental aggregation. Therefore in this thesis a novel sample preparation protocol for native silk is developed and small angle scattering (SAS) techniques are combined with circular dichroism (CD) and atomic force microscopy (AFM) to examine the structure and morphology of the proteins with different mechanical properties and thus biological function in nature. This work highlights the importance of studying native, functional proteins, at close to in vivo conditions, since clear differences in the structure and interaction of native and reconstituted silks can be attributed to the additional processing which reconstituted silks have undergone in order to be solubilised. Indeed native silk proteins are found to be more inherently non-interacting at quite high protein concentrations than reconstituted silk. Upon dilution, inter-chain interactions can be observed by SAS and CD as the protein is driven from its equilibrium conformation. This interaction and the shear-induced assembly of these proteins are also followed by AFM. Interestingly, native silk proteins from spider and silkworms retain a semiflexible conformation in solution. Indeed by comparing the silks from the major and minor ampullate, flagelliform and cylindriform glands of Nephila edulis with the cocoon silk of Bombyx mori silkworms, important insights are gained into how their flexibility suggests similarities in the local environment of the protein chains thereby dictating the hierarchical structure of silk fibres.